ENGLISH CARTOON TASK TO HELP JUNIOR HIGH SCHOOL STUDENTS’ ENGLISH ACQUISITION: FOCUSING ON LISTENING AND SPEAKING - Dian Eka Putri; Kartika Harda Putri (English Language Teaching and Research, 2017)
Language acquisition is started from listening then mimicry and finally the ability to speak. Exposing students with authentic English will help them acquiring, understanding and getting the sense of English better. If the goal is to reach native-like level, being exposed to the authentic English is very important. There are several stages of language acquisition: the receptive or preproduction stage, the early production stage, the speech emergence stage, the intermediate language proficiency stage, the advanced language proficiency stage. English Cartoon Task is meant as extensive activity for the students outside of the school environment. The procedure to be folowed in giving this task: teacher picks a cartoon, teacher distributes the cartoon and task to the students, the students are given some time to watch the cartoon adn do the task, students are asked to present their task. There are several reasons of choosing English Cartoon Task to help students acquiring English. The first reason of using this activity is because it is a fun way to learn English. Second reason is that English cartoon has clear pronunciation. The third reason to use cartoon task is because it uses real life conversation. The fourth reason is because cartoon show has short duration. Several cartoons recommended : Martha Speaks, Word Girl andAdventure Time. Keywords: Cartoon, Task, English Acquisition, Listening, Speaking.